Efficacy and safety of short‐term administration of recombinant human atrial natriuretic peptide (rhANP) for congestive heart failure: a phase II, multicentre randomized controlled dose‐finding study. (14th May 2013) - Wang, P.; Luan, X.; Wang, G.; Liu, W.; Zhang, J.; Li, W.; Gao, X.; Wang, Y.; Mao, Y.; Sun, X.; Wang, Q.; Zhang, Y.; et al.
Summary: What is known and objective: Although the long‐term infusion of ANP has proved effective to treat heart failure, no published randomized controlled study has been reported to confirm the efficacy of the short‐term ANP infusion in congestive heart failure (CHF) patients. This study was designed to assess the efficacy and safety of short‐term infusion of recombinant human atrial natriuretic peptide (rhANP) in CHF patients. Methods: A total of 48 patients with CHF were enrolled and randomized into four groups, treated with standard therapy or rhANP (0·05, 0·1 or 0·2 μg/kg/min) for 1‐hour infusion in addition to standard therapy. The hemodynamics were assessed for 12 h by Swan–Ganz catheter. Results and discussion: The effect of the 0·05 μg/kg/min rhANP dose group on CO was modest and transient. The 0·2 μg/kg/min rhANP dose group tended to be associated with better effect on SV, CO and dyspnoea improvement, but modest effect on PCWP and more adverse events probably attributed to the study drug. However, the 0·1 μg/kg/min rhANP infusion was well tolerated and effective both on PCWP decrease (maximum:−9·46 ± 5·81 mmHg compared with baseline ( P = 0·0002) and −6·75 mmHg compared with standard therapy, the 95% confidential interval [−13·43, −0·06 mmHg] at 1 h) and CO increase (maximum: 1·02 ± 1·43 L/min [ P = 0·0308] at 1 h). What is new and conclusion: In this small‐sample study, 1‐hour infusion of rhANP produced beneficial hemodynamic effects in CHF patients compared with standard therapy, and it was well tolerated. 0·1 μg/kg/min may be the optimum dose for short‐term rhANP infusion to treat CHF for the further large sample trial before clinical application.